The Butter Bump, a Magpie, John Clare - Swann, Karen (Romanticism on the Net, 2019)
The strategies of natural history are distancing ones, and, since Michel Foucault’s The Order of Things, the genre has been the subject of powerful modes of distanced reading. A corollary, perhaps, is that any instance of natural history writing, and especially, any single entry in a natural history compilation, can seem closed to “close” reading: in the field guide as in the taxonomic systems that inform its organization, the highly codified general descriptor, structurally equivalent to every other general descriptor in the set, swallows up the situated, the particular, the near. Within this arena, John Clare’s natural history writing is, in Sara Guyer’s phrase, “hyperbolically local.” Readers have variously praised Clare’s writing on natural subjects for its decentering of an anthropomorphizing perspective, for its mimetic fidelity to an experienced local environment, for what has been described as its proto-environmental or –ecological awareness. This essay pursues the forms of local attentiveness displayed in Clare’s natural history writing in a different direction, to explore how his work engages in close, critical readings of the operations of natural history. My essay tracks Clare’s pursuit of two odd birds, “the” butter bump and “a” magpie, each of which makes a “strange noise” that reverberates through its world, traversing borders, confounding equivalencies, and sounding both the power and the limits of an already-arrived natural order of things.